Nematocidal Activity of Natural Polyphenols from Bryophytes and their Derivatives - Gamenara, Daniela; Pandolfi, Enrique; Saldaña, Jenny; Domínguez, Laura; Martínez, María Mercedes; Seoane, Gustavo (Arzneimittelforschung, 2001)
The nematocidal in vitro activity of three natural perrottetins (phenolic bisbibenz-ylethers) and eleven diphenyl ethers used as synthetic precursors has been assayed using two different experimental models, Caenorhabditis elegans and Nippostrongylus brasiliensis. Nine compounds showed some activity against C. elegans and nine against N. brasiliensis. For the former model, three compounds displayed an activity similar to that of the standards, whereas for N. brasiliensis none of the tested compounds was as active as the standards. From the in vitro results, five compounds (3, 4, 8, 9, 13) could be selected as lead compounds to continue the search for improved activity.
Keywords: Anthelmintics; Bryophytes, in vitro studies, synthesis; Caenorhabditis elegans; Nippostrongylus brasiliensis; Perrottetins, in vitro studies, synthesis